Allergic sensitization prevalence in a children and adolescent population of northeastern Greece region. (October 2016) - Katotomichelakis, Michael; Danielides, Gerasimos; Iliou, Theodoros; Anastassopoulos, George; Nikolaidis, Christos; Kirodymos, Efthimios; Giotakis, Evangelos; Constantinidis, Theodoros C.
Abstract: Objectives: To evaluate the prevalence of allergic sensitization in a childhood and adolescent population, to explore age- and gender-specific variations and finally to discover co-sensitivities among allergens. Methods: A two-stage cross-sectional survey among school-aged children. The two stages of the study involved enrollment of schools and then skin prick testing (SPT) within schools. A total of 675 school children were included in the study. Of those, 231 were diagnosed with allergic rhinitis (AR), according to the medical history as provided by parental-completed questionnaires and positive SPT results. The antigen panel consisted of common allergens and more specifically house dust mites-HDM ( Dermatophagoides farinae and Dermatophagoides pteronyssinus ), grass mix, trees ( olive, cypress and pine ), weeds ( Parietaria spp.), cat and dog epithelium and moulds ( Alternaria spp., Cladosporium spp.). The SPT sensitivity was graded according to SPT-USA Standards. Results: The overall prevalence rate of AR was 34.22%. In total, 93 school children (40.3%) were mono- and 138 (59.7%) were poly-sensitized. Overall, the most prevalent sensitizations in decreasing order were to HDM (59.74%), to grasses (48.9%), to Alternaria (34.6%) and to olive (14.71%). There were no age- and sex-specific differences, except for Alternaria mould that showed a significant prevalence among primary school-aged children and predominance in the female gender, by contrast to grass pollen allergy that was predominant to males. A 32% of SPT-positive individuals were not aware of their allergy, with no statistically significant differences between ages. Co-sensitivities were detected for grass pollens and pine and olive trees, for Alternaria and Cladosporium moulds, for cypress and pine trees, and finally for dog and cat danders. Conclusions: Given data among school-aged children should be a baseline from which to monitor disease trends and is considered important for the optimal management of AR patients.